(untitled) - Parker, Sybil P. (New York, 1994)
This dictionary, last published in 1989, continues to provide clear, concise definitions for the educated general public. The fifth edition has 2,194 pages (57 more than the fourth), 105,100 terms (5,000 more than the fourth), and 3,000 black-and-white photographs (the same as the fourth). It is arranged alphabetically letter by letter, lies flat when open, and is a heavy volume that may present problems in retrieving from the shelf. There are no major changes in the format of this edition.
Keywords: Science,Technology